Microsoft forefront security administration guide - Varsalone, Jesse (Burlington, MA : Syngress Pub., 2008)
Microsoft Forefront is a comprehensive suite of security products that will provide companies with multiple layers of defense against threats. Computer and Network Security is a paramount issue for companies in the global marketplace. Businesses can no longer afford for their systems to go down because of viruses, malware, bugs, trojans, or other attacks. Running a Microsoft Forefront Suite within your environment brings many different benefits. Forefront allows you to achieve comprehensive, integrated, and simplified infrastructure security. This comprehensive suite of tools provides end-to-end security stretching from Web servers back to the desktop. This book will provide system administrators familiar with Syngress' existing Microsoft networking and security titles with a complete reference to Microsoft's flagship security products. * First book to address securing an entire Microsoft network from Web servers all the way back to the desktop. * Companion Web site provides best practices checklists for securing Microsoft operating systems, applications, servers, and databases. * Companion Web site provides special chapter on designing and implementing a disaster recover plan for a Microsoft network.
Part I: Forefront Client Security -- Chapter 1: Introducing Client Security -- Chapter 2: Securing the Desktop -- Chapter 3: Remote Networking and Communications -- Part II: Forefront Security for Exchange Server -- Chapter 4: Securing Client Access -- Chapter 5: Locking Down Exchange Server -- Chapter 6: Backups and Disaster Recovery -- Part III: Forefront Security for SharePoint -- Chapter 7: Securing Sharepoint Servers -- Chapter 8: Secure Communications and Remote Access -- Chapter 9: Defending your Data -- Part IV: Forefront Server Security Management Console -- Chapter 10: Introduction to the Server Security Management Console -- Chapter 11: Exploring the Interface -- Chapter 12: Managing SQL Server and Log Files -- Part V: Microsoft Antigen -- Chapter 13: Defining Malware Defenses -- Chapter 14: Securing the Perimeter -- Chapter 15: Correlating the Results -- Part VI: Microsoft ISA Server 2006 -- Chapter 16: Deploying ISA 2006 in the Enterprise -- Chapter 17: Building a SSL VPN -- Chapter 18: Integrating ISAS Server with Exchange Server -- Part VII: Intelligent Application Gateway 2007 -- Chapter 19: Deploying Application Gateway 2007 -- Chapter 20: Defending your Applications -- Chapter 21: Backup and Disaster Recovery.
Includes index.
Keywords: Microsoft Windows (Computer file).; Computer security; Computer networks -- Security measures; Electronic books